1988
DOI: 10.2307/1591002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cryptosporidiosis and Infectious Bursal Disease Virus Infection of Specific-Pathogen-Free Chickens

Abstract: Specific-pathogen-free chickens orally inoculated at 4 days of age with a moderately pathogenic vaccine strain of infectious bursal disease virus (IBDV) and/or at 5 days of age with Cryptosporidium baileyi oocysts remained free of overt clinical signs throughout a 16-day period postinoculation (PI). The prepatency period for C. baileyi oocyst shedding was shorter in chickens receiving higher numbers of oocysts, but once shedding was detected, there were no obvious differences in shedding patterns among groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…Oral infection by C. baileyi is generally subclinical, although there may be decreased weight gain, which may only be transitory (BLAGBURN et al, 1987;LEVY et al, 1988;MEIRELES et al, 1998a). After oral or intratracheal infection, C. baileyi colonizes the bursa of Fabricius, which presents slight hyperemia and mucus on the mucosal surface.…”
Section: Epidemiological Clinical and Pathological Aspects Of Cryptomentioning
confidence: 99%
See 1 more Smart Citation
“…Oral infection by C. baileyi is generally subclinical, although there may be decreased weight gain, which may only be transitory (BLAGBURN et al, 1987;LEVY et al, 1988;MEIRELES et al, 1998a). After oral or intratracheal infection, C. baileyi colonizes the bursa of Fabricius, which presents slight hyperemia and mucus on the mucosal surface.…”
Section: Epidemiological Clinical and Pathological Aspects Of Cryptomentioning
confidence: 99%
“…Cryptosporidium baileyi causes a severe infection in the bursa of Fabricius (Figure 2b), which is the organ responsible for the humoral immune response in birds (SCOTT, 2004). Although experimental infections with C. baileyi have been found to present diffuse chronic superficial purulent bursitis with epithelial hyperplasia and hypertrophy (Figure 2c) and slight lymphoid atrophy (GUY et al, 1988;LEVY et al, 1988;GOODWIN & BROWN, 1989;MEIRELES et al, 1998b), no influence on the humoral immune response of chickens has been observed (BLAGBURN et al, 1987;MEIRELES et al, 1998b;ABBASSI et al, 2000). Nevertheless, other reports have shown that C. baileyi infection had a suppressive effect on the humoral immune response of birds to the pathogenic virus or vaccine virus for Marek's disease (NACIRI et al, 1989), the Gumboro disease vaccine virus , reoviruses (GUY et al, 1988), the Newcastle disease vaccine virus (RHEE et al, 1998a;ELADL et al, 2014), the infectious bronchitis vaccine virus (RHEE et al, 1998b), Brucella abortus (RHEE et al, 1998c) and the avian influenza vaccine virus (HAO et al, 2008;ELADL et al, 2014).…”
Section: Epidemiological Clinical and Pathological Aspects Of Cryptomentioning
confidence: 99%
“…Avian cryptosporidiosis has been reported in concurrence with immunosupressive viruses like reovirus [113], Marek's disease virus (MDV) [149± 151], infectious bursal disease virus [139,150], and chicken anemia virus [152]. In chickens, the synergistic eect of C. baileyi and these viruses was experimentally con®rmed (reovirus [153] [154], chicken anaemia virus [155]). Marek's disease virus may induce the establishment of the parasite in inhabitual sites ( [156], Abbassi H, Coudert F, Cherel Y, Brugere-Picoux J, Naciri M. Experimental reproduction of renal cryptosporidiosis (C. baileyi) in SPF chickens after oral inoculation of parasite.…”
Section: Interaction With Other Pathogens and Prevalencementioning
confidence: 99%
“…Bursa infections are asymptomatic, and lesions consist of epithelial hyperplasia and infiltration of the epithelium and interstitial tissues by mononuclear cells (Lindsay & Blagburn, 1990). Bursal follicle atrophy has been shown histologically (Levy et al, 1988;Abbassi et al, 1997a) and by measuring relative organ weight proportional to body weight (Abbassi et al, 1997a;Hornok et al, 1998). …”
Section: Introductionmentioning
confidence: 99%